Potato and grape polyphenols, respectively, suppress high-fat diet-elevated oxidative stress/innate inflammation markers in porcine model and induce apoptosis in HCT-116 p53 +/+ and p53 -/- human colon cancer cell lines in vitro - Radhakrishnan, Sridhar, author; Vanamala, Jairam, advisor; Kim, Sung Woo, committee member; Melby, Christopher, committee member; Pagliassotti, Michael, committee member; Veeramachaneni, DN Rao, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: colon inflammation and cancer; pig model; potato; resveratrol; grape seed extract; high-fat diet